2003
DOI: 10.1016/s0191-8869(02)00263-5
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-spatial processing and dimensions of schizotypy: figure-ground segregation as a function of psychotic-like features

Abstract: The aim of the reported study was to determine whether the ability to segregate a simple figure embedded in a complex visual ground, was associated with psychotic-like features in a sample of undergraduate students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
5
19
0
1
Order By: Relevance
“…Table 1 shows the means, SDs, and intercorrelations between the O-LIFE scales. The means and the SDs, as well as the pattern of intercorrelations, were comparable to these reported in the original study on the development of the scales (Mason et al, 1995) as well as to these reported in later studies (e.g., Tsakanikos, 2004;Tsakanikos and Reed, 2003). Preliminary inspection of the detection data revealed that the distributions were negatively skewed (skewness values Ͼ4 times their SEs); therefore, they were logarithmically transformed by employing the Blom estimation formula (͓r -3/8͔/͓w ϩ 1/4͔, where r ϭ rank and w ϭ sum of the case weights).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Table 1 shows the means, SDs, and intercorrelations between the O-LIFE scales. The means and the SDs, as well as the pattern of intercorrelations, were comparable to these reported in the original study on the development of the scales (Mason et al, 1995) as well as to these reported in later studies (e.g., Tsakanikos, 2004;Tsakanikos and Reed, 2003). Preliminary inspection of the detection data revealed that the distributions were negatively skewed (skewness values Ͼ4 times their SEs); therefore, they were logarithmically transformed by employing the Blom estimation formula (͓r -3/8͔/͓w ϩ 1/4͔, where r ϭ rank and w ϭ sum of the case weights).…”
Section: Resultssupporting
confidence: 87%
“…Based on previous studies (e.g., Tsakanikos, 2004;Tsakanikos and Reed, 2003), the typical range of scores on the O-LIFE scales is as follows: Unusual Experiences, 0 -27; Cognitive Disorganization, 0 -22; Introvertive Anhedonia, 0 -15; and Impulsivity Nonconformity, 0 -19.…”
Section: Schizotypy Measuresmentioning
confidence: 99%
“…Table 2 shows the means, standard deviations, and inter-correlations between the O-LIFE scales. The means, standard deviations, and the pattern of inter-correlations were comparable to these reported in the original study on the development of the scales (Mason et al, 1995), and to these reported in later studies (e.g., Tsakanikos & Reed, 2003). The inter-correlations between the O-LIFE scales suggest that most schizotypy symptoms are related to some extent (i.e.…”
Section: Schizotypy Measuressupporting
confidence: 85%
“…The Oxford-Liverpool Inventory for Feelings and Experiences consists of 159 items selected on the basis of factor-analytic studies of older scales assessing psychotic-like features in the general population (Mason, Claridge, & Jackson, 1995). Contributing to the experimental validity of this inventory, various studies have confirmed that high schizotypy scorers, as identified by the O-LIFE sub-scales, demonstrate cognitive deficits similar to those seen in schizophrenic patients (Burch, Steel, & Hemsley, 1998;Goodarzi, Wykes, & Hemsley, 2000;Gray, Fernandez, Williams, Ruddle, & Snowden, 2002;Tsakanikos & Reed, 2003). More specifically, it assesses the following dimensions:…”
Section: Schizotypy Measuresmentioning
confidence: 99%
“…Perceptions of time and space are commonly distorted for the schizophrenic patient, as well as aspects of attention such as figure-ground segregation (Tsakanikos and Reed 2003). Beckett's narrators also demonstrate such distortions of perception, which often compromise the immunity principle and so make difficult ascriptions of ownership to one's sensations and states of mind.…”
mentioning
confidence: 99%